The Strategic Practice of "Fiesta" in a Latino Protestant Church: Religious Racialization and the Performance of Ethnic Identity - Ramos, Aida I. (Journal for the scientific study of religion, 2020)
Founded and led by a U.S.-born white pastor, Amor Poderoso is a nondenominational, evangelical megachurch in El Paso, Texas, almost entirely composed of Mexican-Americans, recent Mexican immigrants, and current Mexican citizens. Ethnographic fieldwork from 2014 to 2017, supplemented with interviews with pastors, worship leaders, and attendees, reveal that much of congregational life orients around intentionally showcasing "Mexican" culture through sounds, images, and artifacts that appropriate an array of idealized ethnic references (e.g., food, dress, mannerisms, clichés) from Northern Mexico. Ongoing ethnic displays do not originate spontaneously or impromptu from membership but rather serve as a form of tactical authenticity derived from U.S. racial schemas mobilized by congregational leaders as a distinctive religious resource. Weekly worship services featuring dialect-inflected Spanish preaching and singing project ethnic signals that elicit connections to both a common ancestral heritage and a common religious identity. In short, church leaders at this southern border Latino church deliberately deploy sounds, images, and artifacts to assert racialized performances of being "Mexican" for distinctly religious purposes, especially evangelization. In the process, the distinctive practices of religious racialization effectively structure church members' ethnic and religious identities around racial tropes to buttress a cogent corporate identity for enacting institutionalized evangelical narratives and legitimating charismatic authority.